FRI0427 IS THE CLINICAL AND THERAPEUTIC PROFILE RELATED TO SATISFACTORY RESPONSE TO APREMILAST IN PSORIATIC ARTHRITIS?. (June 2019) - Morena, Isabel de la; Espinosa, María; Tunidor, Hilda Godoy; Martínez-Ferrer, À; Ramirez, Carlos Santos; Martinez, Anna; Matilla, Meritxell Fernandez; Fernández-Llanio, Nagore; Sanchez, Deseada Palma; Moreno, Maria Jose; Haro, Ana; Conesa, Arantxa; et al.
Abstract : Objectives: To identify the factors that are related with response to Apremilast(APR) in Psoriatic Arthritis(PsA). Methods: An observational and analytical multicenter retrospective study. There are included PsA patients treated with APR after two years of commercialization. Clinical and demographic data were collected: disease duration, previous treatments, cutaneous and joint involvement pattern defined as: joint exclusively, non joint and mixed (by several domains combination). It was collected: duration of treatment, tolerance, adverse events, and reason for APR choice: intolerance or toxicity to csDMARD, preference before bDMARD contraindication or caution to bDMARD, csDMARD and bDMARD inefficacy, csDMARD and bDMARD intolerance. The effectiveness was considered as a dicotomic variable (Yes/No) by clinical criteria. Results: There were included 89 patients, 46(51.7%) males, the mean age was 53.99±12.3 years, and the PsA disease duration was 7.28±6.25 years. The PsA pattern was: joint 29(32.6%), non joint, 12(13.5%) and mixed 48(53.9%). The reason for APR choice was: intolerance or toxicity to cDMARD 13 patients, preference before BT 28, contraindication or caution to BT 22, inefficacy to cDMARD or BT 18, intolerance to cDMARD and BT 1, and due to clinical profile 1. After a mean treatment duration with APR of 8.13(0-23) months a total of 33 withdrawals were found (17 due to inefficacy and 16 due to intolerance), treatment was mantained on them a mean of 4.3(0-12) months. 56 patients keep with APR a mean of 10.4(2-23) months, 22 of them among 1 and 2 years of evolution. The treatment was effective in 61(68.5%) patients. Comparisons of the different variables analyzed did not show significative differences among the responders and non responders patients. Conclusion: We have not found a specific profile that relates with a satisfactory response to APR. Disclosure of Interests: Isabel de la Morena Speakers bureau: Abbvie, Celgene, Pfzier, UCB, Ghebro, Roche, Sanofi, Janssen., María Espinosa: None declared, Hilda Godoy Tunidor: None declared, À Martínez-Ferrer: None declared, Carlos Santos Ramirez: None declared, Anna Martinez: None declared, Meritxell Fernandez Matilla: None declared, Nagore Fernández-Llanio: None declared, DESEADA PALMA SANCHEZ: None declared, Maria jose Moreno: None declared, Ana HARO : None declared, Arantxa Conesa: None declared, Javier Calvo Consultant for: Abbvie, Celgene, Pfzier, UCB, Ghebro, Roche, Sanofi, Janssen, Novartis, Amgen., Speakers bureau: Abbvie, Celgene, Pfzier, UCB, Ghebro, Roche, Sanofi, Janssen, Novartis, Amgen.